Desain dan Simulasi Sistem Pembangkit Listrik Tenaga Bayu Skala Kecil Untuk Penerangan di Perahu Nelayan - Parman, Parman; Tsany, Rahmat Basya Shahrys; Zulfika, Dicki Nizar; Brian, Thomas (LPPM Institut Pendidikan Nusantara Global, 2025)
The utilization of renewable energy in the maritime sector serves as a strategic solution to reduce fishermen's dependence on expensive and environmentally unfriendly fossil fuels. This study develops a mini Wind Power Plant (PLTB) model that can be implemented on fishing boats using a MATLAB Simulink-based simulation approach. The study encompasses turbine aerodynamic design, generator selection, and control system optimization to enhance the efficiency of wind energy conversion into electrical power. Simulation results indicate that at an average wind speed of 7.7 m/s, the designed mini wind turbine is capable of generating 125.8 Watts of mechanical power with a peak torque of 3.44 Nm at a wind speed of 12 m/s. The study also calculates the turbine shaft size at 6 mm, the turbine-side pulley diameter at 70 mm, and the generator-side pulley diameter at 39.63 mm, with a belt drive length of 473.75 mm, based on the generator specifications of 1500 RPM and 81% efficiency. Considering the dynamic maritime environment, the design is evaluated through performance simulations using MATLAB Simulink to ensure power output stability under various wind speed conditions. The analysis demonstrates that the system can maintain wind energy conversion efficiency at optimal wind speeds and has significant potential for small-scale applications.